A Fleet Street In Every Town The Provincial Press in England, 1855-1900 - Hobbs, Andrew (Open Book Publishers, 2018)
"At the heart of Victorian culture was the local weekly newspaper. More popular than books, more widely read than the London papers, the local press was a national phenomenon. This book redraws the Victorian cultural map, shifting our focus away from one centre, London, and towards the many centres of the provinces. It offers a new paradigm in which place, and a sense of place, are vital to the histories of the newspaper, reading and publishing. Hobbs offers new perspectives on the nineteenth century from an enormous yet neglected body of literature: the hundreds of local newspapers published and read across England. He reveals the people, processes and networks behind the publishing, maintaining a unique focus on readers and what they did with the local paper as individuals, families and communities. Case studies and an unusual mix of quantitative and qualitative evidence show that the vast majority of readers preferred the local paper, because it was about them and the places they loved. A Fleet Street in Every Town positions the local paper at the centre of debates on Victorian newspapers, periodicals, reading and publishing. It reorientates our view of the Victorian press away from metropolitan high culture and parliamentary politics, and towards the places where most people lived, loved and read. This is an essential book for anybody interested in nineteenth-century print culture, journalism and reading.